Algunas consideraciones sobre la responsabilidad social empresarial (2011)
This article refers to the dissemination and importance that has taken the social responsibility of companies or corporations. He points out its criteria, its fields of action and attention, where the values underlying their basic purpose. Explores some of the definitions which serve as a support to the questioning that makes social responsibility when it pursues qualitative and quantitative benefits. The content of the text leads to several conclusions which the author hopes to point the meaning of corporate social responsibility, criteria, their values and their recognized importance in contemporary society.